The Evolution of Automation in IT Operations: From Basic Scripts to AI-Powered Solutions - Lokeshwar Reddy Chilla (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The evolution of automation in IT operations represents a transformative journey from basic scripting to sophisticated AI-powered solutions, marking a fundamental shift in how organizations approach their technological infrastructure. This article explores the progression through various stages of automation maturity, examining the impact of modern automation frameworks, container orchestration technologies, and artificial intelligence applications in IT operations. The article investigates key developments in configuration management tools, workflow automation, and enterprise implementation strategies across multiple industries, including financial services, healthcare, e-commerce, and telecommunications. Through detailed examination of real-world case studies and implementation patterns, this article highlights the convergence of traditional automation approaches with emerging technologies such as machine learning, predictive analytics, and AIOps. The article encompasses both technical aspects of automation evolution and organizational considerations, including change management strategies, skill development requirements, and governance frameworks necessary for successful automation initiatives in contemporary enterprise environments.